$$[H,\gamma^\dagger_\alpha]=E_\alpha \gamma^\dagger_\alpha$$
$$[H,\sum_{\nu=1}^n a_\nu c^\dagger_\nu]=\sum_{\nu=1}^n E_\alpha a_\nu c^\dagger_\nu$$
$$\sum_{\nu=1}^n a_\nu[H,c^\dagger_\nu]=\sum_{\nu=1}^n E_\alpha a_\nu c^\dagger_\nu$$
$$\sum_{\nu=1}^n a_\nu[\sum_{\mu,\beta=1}h_{\mu,\beta} c^\dagger_\mu c_\beta,c^\dagger_\nu]=\sum_{\nu=1}^n E_\alpha a_\nu c^\dagger_\nu$$
Here I use the commutator relation for ladder operators: $[AB,C]=A\{B,C\}-\{A,C\}B$ and that $\{\gamma^\dagger_\alpha,\gamma_\beta\}=\delta_{\alpha\beta}$